2021
DOI: 10.1093/icvts/ivab072
|View full text |Cite
|
Sign up to set email alerts
|

Post COVID-19 large pneumatocele: clinical and pathological perspectives

Abstract: A middle aged COVID-19 male patient presented 2 weeks after discharge with new onset of dyspnoea and desaturation. Radiological studies revealed right side pneumothorax and lower lobe cystic air space. Chest drain was inserted and on a later date the patient underwent thoracoscopic surgery where a large pneumatocele was identified. Deroofing and closure of sources of air leak were done. Histopathological examination demonstrated extensive fibrosis, intra-alveolar Haemorrhage and pneumocytes hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 5 publications
0
24
0
1
Order By: Relevance
“…Regarding histological evaluation, Hamad et al reported a thin tissue wall demarcating lesions similar to PHC, with marked fibroblast proliferation, lymphocyte infiltration, intra-alveolar hemorrhage, and pneumocyte proliferation [ 11 ]. According to our findings, the histological changes were similar when the lesion was close to the pleura, but in intrapulmonary cases, the connective tissue surrounding the hematic material showed a reactive inflammatory process secondary to a foreign body, very different from the previous descriptions of COVID-19 lung affection as diffuse alveolar damage, organizing pneumonia, reactive type II pneumocytes, and chronic interstitial pneumonia [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding histological evaluation, Hamad et al reported a thin tissue wall demarcating lesions similar to PHC, with marked fibroblast proliferation, lymphocyte infiltration, intra-alveolar hemorrhage, and pneumocyte proliferation [ 11 ]. According to our findings, the histological changes were similar when the lesion was close to the pleura, but in intrapulmonary cases, the connective tissue surrounding the hematic material showed a reactive inflammatory process secondary to a foreign body, very different from the previous descriptions of COVID-19 lung affection as diffuse alveolar damage, organizing pneumonia, reactive type II pneumocytes, and chronic interstitial pneumonia [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the COVID-19 pandemic has continued worldwide during 2020 and 2021, an increasing number of long-term complications are emerging, such as cardiac affection [1,2], neurologic disorders [3,4], and pulmonary fibrosis [5,6]. Recently, the appearance of characteristic pulmonary lesions has been noted, being described as "giant bulla" [7][8][9] or post-COVID-19 pneumatocele [10,11].…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 Failure of this technique should lead to surgical pneumonostomy 17 or resection. 18 , 19 On the contrary, in critically ill patients, surgical approach seems more reasonable as the first choice of intervention, since it may be life‐saving. In this case, the patient substantively recovered on conservative management without any need for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…To this day, we know only the short-and medium-term results of COVID-19 involvement. It has been reported that the disease causes cystic changes like pneumatocele [11]. Apart from this, when infection occurs in small calibre (<5mm) cystic lesions within GGO areas, it is known as the vacuolar sign [12].…”
Section: Discussionmentioning
confidence: 99%